Quantitative LC/MS/MS analysis of acetaminophen–cysteine adducts (APAP–CYS) and its application in acetaminophen overdose patients - Taha, Hairin; Rahman, Marzilawati Abdul; Haron, Didi Erwandi Mohamad; Mahadeva, Sanjiv; Kee, Lee Yean; Abd Rahman, Noorsaadah; Mohd, Mustafa Ali; Chik, Zamri (Royal Society of Chemistry, 2013)
A more sensitive approach by liquid chromatography–tandem mass spectrometry (LC/MS/MS) method using the AB Sciex QTRAP 5500 was developed and validated for the detection and quantification of acetaminophen–cysteine adducts (APAP–CYS) in human plasma. Chromatographic separation was achieved using a Protecol P C18 column (2.1 mm i.d. × 100 mm, 3 microns). The mobile phase consists of A: 2 mM ammonium formate in water (0.2% formic acid) and B: 2 mM ammonium formate in acetonitrile (0.2% formic acid). The analysis was performed using positive and negative ion electrospray ionization (ESI) in multiple reaction monitoring mode (MRM) with a total run time of 7 min per assay. The MS/MS ion transitions monitored were m/z 271 → 140 for APAP–CYS (positive mode) and m/z 154 → 111 for acetaminophen-D4 (negative mode). The newly developed method showed good linearity in the range of 1.0 to 100 ng mL−1. Inter and intra batch precision and accuracy of the method ranged from 0.28 to 5.30% and 87.0 to 113% respectively. LOD was 0.5 ng mL−1 and LLOQ was 1.0 ng mL−1. Analytes were extracted from plasma samples by simple protein precipitation using acetonitrile. The method was successfully applied in a preliminary clinical study to determine APAP–CYS concentration from 46 acetaminophen overdose patients treated at outpatient clinic in the University Malaya Medical Centre.